Risk Factors of Acute Coronary Syndrome in Adam Malik General Hospital - Jessi Vania Tambarta; Cut Aryfa Andra; Lili Rohmawati; Aryani Atiyatul Amra (SCRIPTA SCORE Scientific Medical Journal, 2025)
Background : Coronary Artery Disease (CAD) has been nominated as the worldâ€™s biggest killer due to its participation in 16% of mortality cases globally. Unstable Angina Pectoris (UAP), Non ST-Elevation Myocardial Infarction (NSTEMI), and ST-Elevation Myocardial Infarction (STEMI) are parts of CAD that united into a term called Acute Coronary Syndrome (ACS). Several risk factors have been linked to ACS phenomenon and categorized into modifiable and in-modifiable risk factors. Objective : This study aims to discover the existing risk factors in ACS patients at Adam Malik General Hospital within 2022-2023 period. Method :  This study is a descriptive with cross-sectional design and retropective approach. The data is a secondary data from medical record that fullfils the criteria. Result : Among the 190 patients, 170 patients (89,5%) were >45 years old, 114 patients (75,8%) were male, 104 patients (54,7%) were smokers, 118 patients (62,1%) had hypertension, 71 patients (37,4%) had diabetes, 65 patients (34,2%) were obese, and 114 patients (60%) had dyslipidemia. Conclusion : The unmodifiable risk factors in this study were age and gender, whilst the modifiable risk factors were smokers, hypertension, diabetes, obese, and dyslipidemia. The most frequent risk factor was hypertension which was found in 60% of the patients Latar belakang : Penyakit Jantung Koroner (PJK) dimobatkan sebagai penyebab kematian terbesar di dunia akibat perannya pada 16% kasus kematian secara global. Angina Pektoris Tidak Stabil (APTS), Non-ST levation Myocardial Infarction (NSTEMI), dan ST-Elevation Myocardial Infarction (STEMI) adalah bagian dari PJK yang disatukan dalam Sindroma Koroner Akut (SKA). Beberapa faktor risiko telah dihubungkan dengan kejadian SKA dan dikategorikan menjadi faktor risiko yang tidak dapat dimodifikasi dan faktor risiko yang dapat dimodifikasi. Tujuan : Penelitian ini bertujuan untuk menelusuri faktor risiko yang terjadi pada pasien SKA di RSUP Haji Adam Malik pada periode 2022-2023. Data yang digunakan adalah data sekunder dari rekam medik yang memenuhi kriteria. Hasil : Dari 190 pasien, 170 pasien (89,5%) berusia >45 tahun, 114 pasien (75,8%) adalah laki-laki, 104 pasien (54,7%) adalah perokok, 118 pasien (62,1%) penderita hipertensi, 71 pasien (37,4%) penderita diabetes, 65 pasien (34,2%) obesitas, 114 pasien (60%) penderita dislipidemia. Kesimpulan : Faktor risiko yang tidak dapat dimodifikasi pada penelitian ini adalah usia dan jenis kelamin, sementara faktor risiko yang dapat dimodifikasi adalah perokok, hipertensi, diabetes, obesitas, dan dislipidemia. Faktor risiko yang paling banyak terjadi adalah hipertensi yang didapatkan pada 60% pasien